An Appraisal of the Nature of Islamic Criminal Procedure: Whether Adversarial or Inquisitorial? (Al-Qamar, 2024)
Criminal procedure is criminal justice in action. Islamic Criminal law (ICL) is being enforced through western procedural systems known as adversarial and inquisitorial which makes significant anomaly in the application of ICL. Enforcement of ICL without accompanying Islamic rules of procedure is arguably to practice ICL incompletely, inaccurately, and indeed un-Islamically. As the substantive ICL is different in its form and substance, the Islamic Criminal Procedure (ICP) is also different than the western procedural models. The ICP has many independent features which are not available in any other law. The classification of offences in ICL is linked with violation of rights; of Allah, of the individual and of the society. The kind of right violated determines the rules of procedure. Furthermore, Islamic law operates within two spheres; fixed and flexible. The Muslim jurists worked on fixed part whereas care of flexible part is left in the hand of rulers. Although the rules of ICP can be found in Qur’ān & Sunnah – primary sources of Islamic law - and in classical Islamic jurisprudence but neither the classical nor the contemporary Muslim scholars set out formal code of ICP (templates) corresponding code of procedure of modern-day. By applying qualitative research methodology, this article aims to examine the nature of ICP whether adversarial or inquisitorial while examining its salient features. It discusses classification of ICP and analyzes legal consequences of its various kinds. Scientific study of ICP can play vital role to direct our ongoing revamping process of criminal justice in the right direction with the aim to make the system efficient and cost-effective in the delivery of expeditious justice.
Keywords: Adversarial; Criminal Procedure; Islamic Criminal Procedure; Inquisitorial; violation of right; ta‘zīr